Single and binary adsorptions of heavy metals onto activated carbon - equilibrium studies - Muhammad,; Jamari, Saidatul Shima; Chuah, Teong Guan; Abdul Rashid, Suraya; Choong, Thomas Shean Yaw (Federation of Engineering Institutions of Islamic Countries, 2006)
A series of batch laboratory studies were conducted in order to investigate the suitability of Norit activated carbon grade SA2 for the removal of cadmium ions and zinc ions from their aqueous solutions. The single component equilibrium data was analyzed using the Langmuir and Freundlich isotherms, respectively. Overall, the Langmuir isotherm showed the best fit for all adsorptions under investigation in terms of correlation coefficient as well as error analysis. As the binary adsorption is competitive, the extended Langmuir (EL) models does not predict well the binary component isotherm. The modified extended Langmuir (MEL) models were used to fit binary system equilibrium data and reasonable fitting was observed.